Climate change literacy and migration potential: micro-level evidence from Africa - Marc Helbling; Daniel Auer; Daniel Meierrieks; Malcolm Mistry; Max Schaub (Climatic Change, 2021)
While a growing literature studies the effects of climate change on international migration, still only relatively little is known about the individual mechanisms linking migration decisions to climate change. We argue that climate change literacy (i.e., knowledge about climate change) is a major determinant of why some individuals consider migrating to other countries in response to climate change effects. In particular, climate change literacy helps individuals translate their perceptions of temperature changes into an understanding of these changes' irreversible long-term consequences. We test this hypothesis using highly accurate geo-coded data for 37,000 individuals across 30 African countries. We show that climate change indeed leads to stronger migration intentions among climate literates only. Furthermore, we show that climate change only increases migration intentions among climate literates when it is approximated by long-run increases in local temperatures, but not when operationalized as changing heat wave or precipitation patterns. Further analyses show that climate literates are more likely to live in urban areas, have a higher news consumption, are highly educated, and have demanding occupations. Consequently, climate change may further deprive affected countries of valuable talent.
Keywords: 320; international migration; migration intentions; climate change; climate change literacy; Africa